Customer winback : how to recapture lost customers and keep them loyal - Griffin, Jill (Jossey-Bass business & management series., 2001)
Most firms consider the lost customer a lost cause. But in this ground breaking book, Jill Griffin and Michael Lowenstein provide you with step-by-step solutions for winning back lost customers, saving customers on the brink of defection, and making your firm defection proof. Whether your business is small or large, product- or service-based, retail or wholesale, this book offers proven strategies for recognizing which lost customers have the highest win-back value and implementing a sure-fire plan to recover them. It includes the techniques of hundreds of innovative companies who are already.